KASHMIR VALLEY AS A TIMELESS TOURIST DESTINATION: A HISTORICAL STUDY - Dr. Shabir Ahmad Lone; Dr. Indira P Suryavanshi; Dr. Javad Ahmad Mir (RADJA PUBLIKA, 2026)
Kashmir Valley has long been celebrated as a timeless tourist destination, attracting travelers, pilgrims, scholars, and rulers across centuries. This qualitative study explores the historical evolution of tourism in the Kashmir Valley by examining travel accounts, historical texts, cultural traditions, and heritage sites. From ancient times, Kashmir served as a center of spiritual pilgrimage, learning, and natural retreat, drawing visitors due to its scenic landscapes, sacred shrines, and rich cultural life. During the medieval period, Sufi traditions, Mughal patronage, and artistic developments further enhanced the valley’s appeal. In the colonial and post-colonial eras, Kashmir emerged as a prominent leisure destination, shaping modern tourism infrastructure while retaining its historical charm. The study highlights how geography, culture, spirituality, and hospitality collectively contributed to Kashmir’s enduring tourist identity. By emphasizing continuity and transformation, the paper underscores the historical depth of tourism in Kashmir Valley and its significance in understanding the region’s cultural and economic heritage.